(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In this article, heart failure is a condition in which the heart does not pump enough blood to the rest of your body. If your heart is damaged or isn’t pumping properly, it can become enlarged, weak, or stiff about his illness.